Pengaruh Harga, Brand Experience, Dan Kecepatan Pengiriman Terhadap Loyalitas Konsumen Dimediasi Customer Review Dan Di Moderasi Konten Kreator Pada Konsumen Tik Tok Di Kota Sumenep - Zakki, Nurdody; Fathorrahman, Fathorrahman; AS, Fathor (Trunojoyo University of Madura, 2025)
The study aims to analyze the effect of price, brand experience, delivery speed, customer reviews, and content creators on TikTok consumer loyalty in Sumenep City. The research approach is quantitative with the Structural Equation Modeling (SMART-PLS) path analysis method. Data collection techniques use questionnaires with Google Form techniques. The sample in this study amounted to 96 respondents using the Lemeshow formula. The sampling technique was non-probability sampling with an accidental sampling approach. The results showed that the variables consisting of; price, brand experience, delivery speed, customer review, and creator content have a significant influence on consumer loyalty. Price, brand experience, delivery speed, and customer reviews have a strong positive influence on loyalty, and creator content is also proven to make a significant contribution to consumer loyalty. The mediation analysis results show that content creators play a partial moderating role in the relationship between price and delivery speed with consumer loyalty but do not play a moderating role in the relationship between brand experience and loyalty. These findings provide new insights into the factors that shape consumer loyalty on social media platforms such as TikTok Shop, as well as the strategic role of content creators in building emotional connections. The practical implications of this research can serve as a basis for academics to design more effective marketing strategies by involving content creators and optimizing customer reviews on the TikTok Shop platform.